PENGARUH PEMANFAATAN PERPUSTAKAAN DAN MINAT BELAJAR TERHADAP PRESTASI BELAJAR SISWA AKUNTANSI SMK NEGERI 10 JAKARTA - DIANTY RAHMAWATI; ATI SUMIATI (Jurnal Ilmiah Econosains, 2015)
Abstract This research was aimed to obtain valid and reliable data aboutLibrary Utilization and Interest Learning with learning achievement of accounting in class XI accounting SMK Negeri 10 Jakarta. This research was conducted by survey method and correlational approach.Sampling technique used proportional random sampling.Affordable population in this research wereGrade XI Accounting students with totaling 66 students. Total of samples used were 58 students. The results showed that: there is a positive relationship between Library Utilization with learning achievement and Interest Learning with learning achievement of XI Accounting student in Vocational High School 10 Jakarta. Thus if the Library Utilization and Interest Learning increases, the Learningachievement will also increase. Keywords: Library Utilization, Interest Learning, LearningAchievement